Mydin transformation focus: leadership and organizational change - Nik Muhammad, Nik Maheran; Md Isa, Filzah; Othman, Siti Norezam (Emerald Group Publishing Limited, 2011)
The case study highlights a successful retail business leader who has been directly involved in the transformation of his family business from a mere merchandiser to hypermarket owner. For more than five decades of developing and cultivating his leadership skills, business competencies and continuous learning, he successfully competes with foreign giant retailers. To comprehend the transformation process undergone by his business, the case study captures the development phases of the organizational changes and the leader's leadership and decision-making styles from the early establishment of the company until becoming a local giant retailer, that is chosen as a ”value for money” merchandiser by the customers.